2024
DOI: 10.3389/fmars.2023.1320540
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan diversity and community assemblages in sediments across a Western Pacific Trench-Arc-Basin system: insights from eDNA metabarcoding

Jing Mo,
Xinlong Li,
Anning Mou
et al.

Abstract: Trench-arc-basin (TAB) systems are widely distributed in the deep sea, yet our understanding of their biodiversity patterns and community assemblages remains limited. In this study, we collected sediment samples from 22 stations across a Western Pacific TAB system and identified 85 families of marine benthos from 15 phyla by using eDNA metabarcoding with the 18S rRNA gene V4 region. Nematodes were the most dominant metazoan taxa followed by echinoderms, arthropods, and annelids. The highest biodiversity and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…We were unable to detect ASVs belonging to the phylum Porifera, commonly known as sponges, which are vulnerable to the impacts of anthropogenic activities in seawater samples collected from the western Pacific Ocean. Previous studies have also reported limited occurrences of Porifera in a small proportion of nodules and sediments (Kitahashi et al, 2020;Laroche et al, 2020a;Lejzerowicz et al, 2021;Mo et al, 2024), but they were noticeably absent in metazoan communities in seawater samples, even when using both 18S and COI markers (Laroche et al, 2020a). This discrepancy may be associated with various characteristics of eDNA released into seawater by different species such as shedding rate, particle size, and stability in the environment, all of which can influence degradation rates (Kwong et al, 2021;Zhao et al, 2021;Hinz et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…We were unable to detect ASVs belonging to the phylum Porifera, commonly known as sponges, which are vulnerable to the impacts of anthropogenic activities in seawater samples collected from the western Pacific Ocean. Previous studies have also reported limited occurrences of Porifera in a small proportion of nodules and sediments (Kitahashi et al, 2020;Laroche et al, 2020a;Lejzerowicz et al, 2021;Mo et al, 2024), but they were noticeably absent in metazoan communities in seawater samples, even when using both 18S and COI markers (Laroche et al, 2020a). This discrepancy may be associated with various characteristics of eDNA released into seawater by different species such as shedding rate, particle size, and stability in the environment, all of which can influence degradation rates (Kwong et al, 2021;Zhao et al, 2021;Hinz et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…We were unable to detect ASVs belonging to the phylum Porifera, commonly known as sponges, which are vulnerable to the impacts of anthropogenic activities in seawater samples collected from the western Pacific Ocean. Previous studies have also reported limited occurrences of Porifera in a small proportion of nodules and sediments (Kitahashi et al, 2020;Laroche et al, 2020a;Lejzerowicz et al, 2021;Mo et al, 2024), but they were noticeably absent in metazoan communities in seawater samples, even when using both 18S and COI markers (Laroche et al, 2020a). This discrepancy may be associated with various characteristics of eDNA released into seawater by different species such as shedding rate, particle size, and stability in the environment, all of which can influence degradation rates (Kwong et al, 2021;Zhao et al, 2021;Hinz et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Abyssal ecosystems are strongly influenced by the influx of detrital organic materials originating from the ocean surface owing to limited food availability on the abyssal seafloor (Smith et al, 2008). Mo et al (2024) demonstrated a positive correlation between total organic carbon (TOC) levels and Cnidaria abundance, which supports previous studies indicating taxa-specific effects of TOC on megafaunal diversity (Levin and Gage, 1998;Cunha et al, 2011;Nishijima et al, 2015). However, in our study area, we observed no statistically significant differences in the TOC levels between the seamounts and the adjacent abyssal plains, with relatively low TOC levels detected in the abyssal plains (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to detect ASVs belonging to the phylum Porifera, commonly known as sponges, which are vulnerable to the impacts of anthropogenic activities in seawater samples collected from the western Pacific Ocean. Previous studies have also reported limited occurrences of Porifera in a small proportion of nodules and sediments (Kitahashi et al, 2020;Laroche et al, 2020a;Lejzerowicz et al, 2021;Mo et al, 2024), but they were noticeably absent in metazoan communities in seawater samples, even when using both 18S and COI markers (Laroche et al, 2020a). This discrepancy may be associated with various characteristics of eDNA released into seawater by different species such as shedding rate, particle size, and stability in the environment, all of which can influence degradation rates (Kwong et al, 2021;Zhao et al, 2021;Hinz et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Abyssal ecosystems are strongly influenced by the influx of detrital organic materials originating from the ocean surface owing to limited food availability on the abyssal seafloor (Smith et al, 2008). Mo et al (2024) demonstrated a positive correlation between total organic carbon (TOC) levels and Cnidaria abundance, which supports previous studies indicating taxa-specific effects of TOC on megafaunal diversity (Levin and Gage, 1998;Cunha et al, 2011;Nishijima et al, 2015). However, in our study area, we observed no statistically significant differences in the TOC levels between the seamounts and the adjacent abyssal plains, with relatively low TOC levels detected in the abyssal plains (unpublished data).…”
Section: Discussionmentioning
confidence: 99%